A novel Sustainable Development Goal 7 composite index as the paradigm for energy sustainability assessment: A case study from Europe. (1st February 2022) - Madurai Elavarasan, Rajvikram; Pugazhendhi, Rishi; Irfan, Muhammad; Mihet-Popa, Lucian; Campana, Pietro Elia; Khan, Irfan Ahmad
Highlights: Proposed a novel SDG 7 composite index for assessing energy sustainability. Dimensions include clean energy, security, emission, intensity, accessibility. Proposed ANMMO normalization method to reduce the influence of outliers. SDG 7 composite index depicts a more accurate reality than the actual SDG 7 index. Iceland, Norway, and Sweden tops in energy sustainability aspects. Abstract: The Sustainable Development Goal 7 endeavors to ameliorate the energy system towards sustainability. Monitoring the country's progress to the goal will be of utmost for the government to take suitable actions and thus, constructing a performance monitoring index for Sustainable Development Goal 7 would tune the pace of implementation. This study aims to develop a novel Sustainable Development Goal 7 or Energy Sustainability Composite Index to assess the energy sustainability performance. Since Europe tends to have diverged efforts towards energy sustainability, assessing them with the proposed Sustainable Development Goal 7 composite index would provide the evidence needed for effective sustainable development strategies. By describing Europe, the authors signify 40 European countries and the selection of country depends on the availability of all the data that are required for the energy sustainability assessment. In this study, the analyzed energy sustainability aspects include clean energy conversion, energy security, energy accessibility, energy intensity and carbon intensity. The results show that Iceland, Norway, and Sweden tops in energy sustainability aspects with scores of 0.7313, 0.6967, and 0.6313 (on a scale of 0 to 1), respectively. The proposed Sustainable Development Goal 7 composite index is also compared with the actual Sustainable Development Goal 7 index, which comprises the indicators defined by the United Nations. The prime difference between the proposed Sustainable Development Goal 7 composite index and the actual Sustainable Development Goal 7 index resides in the consideration of energy security and carbon intensity indicators and in the framework designed to evaluate the clean energy prevalence. The evaluated actual Sustainable Development Goal 7 index scores of Germany and France are 0.4915 and 0.4656, respectively. On comparing with the proposed Sustainable Development Goal 7 composite index scores, the scores decreased by 20.9% for Germany and increased by 7.2% for France. The robustness of the proposed composite index relies on reducing the effect of outliers by using a modified min–max methodology, namely Aggregated Normalization based on Maximum and Minimum Outliers for normalization and the subsequent weightage allocation criteria utilized in Analytic Hierarchy Process methodology. Sensitivity analyses highlighted that the clean energy indicator is the most influencing indicator for the designed composite index. Nevertheless, uncertainty analysis indicates that the weightage scenario has a more prominent influence than various normalization and aggregation methods.